Frequency of bovine viral diarrhea virus (BVDV) in Argentinean bovine herds and comparison of diagnostic tests for BVDV detection in bovine serum samples: a preliminary study - Spetter, Lucas Maximiliano (2020)
Bovine viral diarrhea (BVD) is a major worldwide disease with negative economic impact on cattle production. Successful control programs of BVD require the identification and culling of persistently infected (PI) animals with bovine viral diarrhea virus (BVDV). A variety of diagnostic tests are available to detect BVDV, but no comparison has been performed among those tests in Argentina. Sera collected from 2864 cattle, belonging to 55 herds from three Argentinean provinces, were analyzed by nested RT-PCR (RT-nPCR) to detect BVDV for diagnostic purposes. Additionally, this study evaluated the agreement of the RT-nPCR along with virus isolation, antigen-capture ELISA, and real-time RT-PCR for BVDV detection in archived bovine serum samples (n = 90). The RT-nPCR was useful for BVDV detection in pooled and individual serum samples. BVDV was detected in 1% (29/2864) of the cattle and in 20% (11/55) of the herds. The proportion of BVDV-positive sera was not statistically different among the tests. In addition, comparisons showed high agreement levels, with the highest values between both RT-PCR protocols. The frequency of BVDV infection at individual and herd level was lower than the reported values worldwide. Since follow-up testing was not performed, the frequency of PI cattle was unknown. Also, this study demonstrated that the four diagnostic tests can be used reliably for BVDV identification in individual serum samples. Further epidemiologically designed studies that address prevalence, risk factors, and economic impact of BVDV in Argentina will be necessary to implement effective control programs.